Cinética e proposta de análise da temperatura da pele de membros inferiores em atletas de futebol profissional - Alex de Andrade Fernandes (2017)
The skin temperature (TSK) evaluated through infrared thermography (IRT) a noninvasive way of measuring one of the body's responses (heat) to the inflammatory process and can therefore be a variable associated with muscle damage, which can be used as a strategy to control training in high-performance athletes. Thus, the objectives of this study are: to analyze the kinetics of lower limbs TSK in elite soccer athletes, after participation in official matches, at moments M1 - (Pre-Game), M2 - 24 hours after the game; M3 - 48 hours after the start of the match; verify the possible correlation between TSK with the individualized percentage of creatine kinase (CK); to compare the body regions of interest (RCIs) on the right side with left, as well as the anterior and posterior view; to present a new methodology for lower limbs TSK analysis based on the quantification of the number of pixels stratified by temperature ranges and temperature reference zones; besides analyzing the total number of pixels in the right and left legs in the anterior and posterior views in the different moments studied. For this purpose, the sample consisted of thirty (30) soccer athletes belonging to a professional club of the first division of Brazilian soccer, and the data collection of CK and TSK was performed in the three moments indicated previously, throughout the seasons 2015 , seven (7) matches and the 2016 season six (6) matches of the Brazilian Serie A Football Championship. The results indicate that the TSK of all the RCIs is statistically significant (P <0.001) higher in the M2, with ≅ 1.5 °C higher in the RCIs of the thighs and legs in the anterior view and ≅ 2.0 °C in the thighs in the (P <0.001) in M3, but not yet statistically enough to return to the condition presented in M1. Participation in a football match does not cause asymmetry between the among the RCIs at all times studied. In the comparison between RCIs in the anterior and posterior view, it can be observed that there was a significant difference (P <0.001), mostly at moments M1 and M3, with variations of ≅ 0.4 °C, with the exception of moment M2. There is a significant and moderate positive correlation between TSK recorded in all RCIs with CK being the lowest (r = 0.52; P <0.001). The application of this new methodology based on the stratification of the number of pixels separated by temperature ranges and reference zones are sensitive to the physiological changes that occur in function of the matches, and provide greater agility, contemplation of all anatomical areas of the muscles, without the need to draw markers thermal images. In this way, it is concluded that the TSK of lower limbs presents a behavior over time similar to that of CK, with increase 24 hours after the accomplishment of the departures and tendency of reduction in M3, but not yet sufficient to return the condition presented pre-game thus this new methodology called “thermopixelgraphic” here can be used in software and specific programs aimed at assisting in the process control of training load, injury prevention and monitoring of the recovery process in soccer players.